Learning style corner method: REAPSES - Castellanos, Reina (Journal of Learning Styles, 2020)
This research aims for education to have a new alternative in teaching, transforming the space without cost and with educational impact, at all educational levels. Being of interest to the present times, where learning is not only receptive and memoristic, but significant.Students, future primary school teachers of the years 2017, 2018 and 2019 participate. A selective methodology is used with an ex post facto, transversal and cross-sectional design. It has been found that pragmatic, reflective and active styles predominate, in addition, observing an increase in the average grade in the course, which is worked with the REAPSES method. It is advisable to change the educational relationship between the university and the academic training centers, promoting synergies and cooperation, assuming an individualized pedagogy of the student taking into account his/her learning styles.